Application of ICT, b-Learning, and Computational Thinking for the Strengthening of Mathematical Competencies (Docentes 2.0 Journal, 2022)
Mathematics is a well-known disliked subject in junior high school, as indicated by poor grades and low passing rates. In addition, the PISA data show that Colombian students perform poorly in solving mathematical problems, with lower statistical results than expected. The general purpose of this study is to evaluate the effectiveness of the didactic model based on b-Learning, computational thinking fostered in gamification, and disconnected activities to strengthen the learning of competence and solve mathematical problems in Tumaco secondary school students. The research is based on the hypothetical-deductive method, positivist paradigm, with a quantitative approach, experimental design, quasi-experimental field type, and cross-sectional. Made up of a control group and experimental group; the data collection is a sample of 28 students; the data collection is the technique and instruments such as questionnaires: diagnostic evaluation (pretest), final evaluation (posttest) in which the comparisons in the performance of the planned activities, a satisfaction form was applied to the students, where the impact and perception of the entire process in which they will be immersed were evidenced. Finally, this didactic model is a technological instrument to improve teaching-learning activities. In addition, using the didactic model and computational thinking strategies will improve the motivation of students to learn mathematics.
Keywords: b-Learning; computational thinking; ICT; skills; mathematics